PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR CONSUMER NON-CYCLICALS - Kanina Riana Damaputri (2022)
The purpose of quantitative in this research is to assess the influence of financial performance on firm value. There are three variables that are used in this study to measure financial performance: liquidity, activity and profitability. This research was conducted in the consumer non-cyclicals sector which was listed on the Indonesia Stock Exchange (IDX) in 2017-2021. This research used the purposive sampling method with predetermined criteria for sampling, which resulted in 35 companies being sampled. The data analysis method used in this research was panel data regression analysis using E-views 12 application. By using firm value as measured price book value (PBV), this research found that (1) Liquidity as measured by current ratio (CR) has no effect on firm value as measured using price book value (PBV), (2) Activity as measured by inventory turnover (ITO) has an effect on firm value as measured by price book value (PBV), and (3) Profitability as measured by return on equity (ROE) has no effect on company value as measured using price book value (PBV).